2020
DOI: 10.1002/eat.23442
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for anorexia nervosa and bulimia nervosa in Japan and compared to a U.S. sample

Abstract: Objective This study provides the first systematic investigation of environmental exposure to putative psychosocial risk factors for eating disorders in individuals with AN and BN in Japan. It also provides a comparison of risk factors for the development of AN and BN in Japan versus the United States. Method Participants in Japan were 96 women with a current DSM‐IV AN or BN primary diagnosis (AN, n = 60; BN, n = 36) and 57 women with no current psychiatric diagnosis (NC group). Participants in the United Stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 52 publications
1
13
0
Order By: Relevance
“…As far as the presence of other disorders in family members is concerned, our review established that a familiar history of almost any psychiatric disorder Pike et al, 2021), including depression (Lyon et al, 1997), affective disorders (Steinhausen et al, 2015), alcohol and drug abuse (Lyon et al, 1997) plays a role in the development of AN. Nevertheless, having a sibling with AN increases the risk of developing AN (Machado et al, 2014;Steinhausen et al, 2015).…”
Section: Case Controlmentioning
confidence: 89%
See 3 more Smart Citations
“…As far as the presence of other disorders in family members is concerned, our review established that a familiar history of almost any psychiatric disorder Pike et al, 2021), including depression (Lyon et al, 1997), affective disorders (Steinhausen et al, 2015), alcohol and drug abuse (Lyon et al, 1997) plays a role in the development of AN. Nevertheless, having a sibling with AN increases the risk of developing AN (Machado et al, 2014;Steinhausen et al, 2015).…”
Section: Case Controlmentioning
confidence: 89%
“…Perfectionism (Hilbert et al, 2014;Pike et al, 2008Pike et al, , 2021 is widely recognized as a familiar risk factor across many studies, and it can be assimilated to higher parental demands (Pike et al, 2008). It surely contributes to creating a tense family environment in which the development of oneself is more difficult, therefore inhibiting progressive differentiation of self from other (Charles, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on risk factors suggests a complex interaction of biological (Striegel-Moore and Bulik, 2007) and genetic vulnerabilities (Bulik et al, 2016), temperamental variables (Lilenfeld, 2011;Wagner and Vitousek, 2019), family dynamics (Striegel-Moore et al, 1986), and general sociocultural pressures (Striegel-Moore et al, 1986;Wertheim and Paxton, 2011). Though these psychosocial risk factors have been studied mostly in Western and White populations, research has suggested similar correlates in other national, racial, and ethnic groups (Keel and Forney, 2013;Pike et al, 2020). According to Striegel-Moore and Bulik (2007), "the single best predictor for developing an eating disorder is being female" (p. 182).…”
Section: Risk Factors For Eating Disordersmentioning
confidence: 99%